Maternal impressions and colour heredity - Brown, David (The University of Edinburgh, 1911)
I. A maternal impression has no influence in colour inheritance to produce a colour de novo.

II. A maternal impression may influence the proportion in which certain colours, the result of known crosses, are expected to appear.

III. There is no evidence to show that, even if a maternal impression have this power, the resultant colour is necessarily similar to the colour producing the impression.